Effect of Spatholobus littoralis Hassk. Extract on F2-isoprostane Levels as a Marker of Oxidative Stress in Diabetic Rat Models - Ervi Audina Munthe; Siti Khaerunnisa; Gwenny Ichsan Prabowo; Arifa Mustika; Lilik Herawati; Ryota Hosomi (Biomolecular and Health Science Journal)
Introduction: Type 2 diabetes mellitus (T2DM) is a global metabolic disorder affecting 537 million adults, with projections indicating an increase to 783 million by 2045. Oxidative stress, resulting from elevated reactive oxygen species under hyperglycemic conditions, contributes to the pathogenesis of T2DM. Spatholobus littoralis Hassk. (SLH) (bajakah tampala), a traditional herbal plant from Central Kalimantan, contains antioxidant and antidiabetic compounds such as flavonoids, saponins, tannins, and phenols. These compounds delay binding free radicals and stabilize hydroxides that suppress oxidative stress conditions. This study evaluates the effects of SLH stem extract on hepatic F2-isoprostane levels in streptozotocin-induced diabetic rats to assess its potential to reduce oxidative stress. The research employs a true experimental design. Methods: SLH stems were macerated in 96% ethanol. Twelve-week-old male Wistar rats (150–200 g) were acclimatized for 7 days. Diabetes was induced using streptozotocin (35 mg/kg body weight intraperitoneally) and repeated after 7 days. Rats were divided into standard control, negative control, and treatment groups (150, 300, and 450 mg/kg BW extract). Hepatic F2-isoprostane levels were measured using an enzyme-linked immunosorbent assay kit with a microtiter reader at 450 nm. Data were analyzed using Kruskal–Wallis and Mann–Whitney U-tests (SPSS v26), with P < 0.05 considered meaningful. Results: SLH extract showed reduced F2-isoprostane levels (P = 0.000), particularly at 150 mg/kg BW and 450 mg/kg BW, and demonstrated potential in promoting body weight recovery in streptozotocin-induced diabetic rats. Conclusions: SLH stem extract demonstrates potent antioxidant properties, reducing liver oxidative stress and partially improving metabolic recovery in diabetic rats.